1984
DOI: 10.1177/00220345840630090501
|View full text |Cite
|
Sign up to set email alerts
|

Anti-bacterial Determinants of Stannous Fluoride

Abstract: The growth of bacteria on stainless steel wires was used as a model to investigate which properties of SnF2 produced anti-bacterial effects against S. mutans. Wire-adherent bacteria were exposed for one min, twice a day, to various fluoride or control compounds having similar ions, pH, valence, or atomic weights. After two days, the thickness of adherent bacteria was scored visually, and the decrease in pH of the growth medium was determined. Bacteria from each wire were then dried, weighed, and analyzed for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 28 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…Regrowth could have been slowed down by residual CHX bound to dead cells and enamel [Baca et al, 2012;Babu and Garcia-Godoy, 2014]. Stannous can alter S. mutans growth and metabolism [Mayhew and Brown, 1981;Camosci and Tinanoff, 1984] as well as inhibit bacterial adhesion/plaque formation and acid production [Tinanoff et al, 1976;Skjorland et al, 1978], potentially retarding biofilm development and altering its architecture, as observed in our system ( fig. 3 ).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Regrowth could have been slowed down by residual CHX bound to dead cells and enamel [Baca et al, 2012;Babu and Garcia-Godoy, 2014]. Stannous can alter S. mutans growth and metabolism [Mayhew and Brown, 1981;Camosci and Tinanoff, 1984] as well as inhibit bacterial adhesion/plaque formation and acid production [Tinanoff et al, 1976;Skjorland et al, 1978], potentially retarding biofilm development and altering its architecture, as observed in our system ( fig. 3 ).…”
Section: Discussionmentioning
confidence: 64%
“…Because the antibacterial activity of stannous ions is well known [Mayhew and Brown, 1981;Camosci and Tinanoff, 1984;Zameck and Tinanoff, 1987], its presence in the SnF 2 -containing toothpaste suggests that it is the responsible ingredient for the antimicrobial/antibiofilm effect observed with this formulation ( fig. 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The error of measurement reported for both clinical examiners in this paper also corresponds with those values previously reported (Glavind and Loe, 1967 (Tinanoff, 1985). Because the antibacterial activity of SnF2 appears to be related to the availability of Sn2+ ions Camosci and Tinanoff, 1984;Attramadal and Svatun, 1980), these differences may be of significance when these gels are used for control of gingivitis. Camosci and Tinanoff (1984) also showed that other heavy metal ions and Sn3+ ions are not as effective as the Sn2+ ion, and that the mechanism for the bactericidal activity of Sn2+ appeared to be related to intracellular retention of tin by the bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…These effects appear to be related to the availability of the Sn2+ ion rather than the F-ion (Camosci and Tinanoff, 1984). Other clinical reports have demonstrated that topically applied SnF2 is associated with reduction of supragingival plaque, motile subgingival plaque micro-organisms, gingivitis, and pocket depth (for review, see Boyd et al, 1985).…”
Section: Introductionmentioning
confidence: 99%